Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1136/bmj.294.6563.24
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy and acceptability to patients of a physiotherapist working in a health centre.

Abstract: The records of the first 805 patients who had been referred by general practitioners at this health centre to the attached physiotherapist were examined in November 1985, three years after the physiotherapy department was opened. Seventy per cent (549) of the patients had been treated within one week, treatment having started on the same day for 8-5% (67) of the patients. This compares with a mean of six weeks for direct access to a district general hospital that is eight miles away and between six and 13 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 2 publications
0
15
1
1
Order By: Relevance
“…6 The determinants of physiotherapy utilization found in the study (shown in Figure 2) were not consistent with those found in a 1985 British study. 8 While knee problems accounted for 16.5% of all physiotherapy visits in the British study, the corresponding rate in the present study was 5.5%. The proportions of physiotherapy utilization due to spine problems were 24.5% and 41.7% in the British and the present study, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…6 The determinants of physiotherapy utilization found in the study (shown in Figure 2) were not consistent with those found in a 1985 British study. 8 While knee problems accounted for 16.5% of all physiotherapy visits in the British study, the corresponding rate in the present study was 5.5%. The proportions of physiotherapy utilization due to spine problems were 24.5% and 41.7% in the British and the present study, respectively.…”
Section: Discussioncontrasting
confidence: 50%
“…[1][2][3][4][5] The current annual incidence in the United Kingdom is approximately 250,000 new patients per year, 3 and in the United States, it is estimated to be as high as 1 million new cases annually. 5 Out of all claims for personal injury in the United Kingdom, 85% are related to whiplash injury, 6 and the litigation cost is approximately 3 billion British pounds per year.…”
mentioning
confidence: 99%
“…Innovative schemes such as the attachment of a physiotherapist to a primary health care centre may not benefit the elderly, because of attention being diverted to younger patients and the lack of a team structure. 54 Hospital working methods may also be inappropriate because of potential communication difficulties between team members.…”
Section: Many Advantagesmentioning
confidence: 99%